2012
DOI: 10.3928/00989134-20120507-50
|View full text |Cite
|
Sign up to set email alerts
|

Improving Medication Management Among At-Risk Older Adults

Abstract: Low health literacy is common among Medicare recipients and affects their understanding of complex medication regimens. Interventions are needed to improve medication use among older adults, while addressing low health literacy. Community-dwelling older adults in this study were enrolled in an inner-city adult day center. They completed a baseline measure of health literacy, medication self-efficacy, and medication adherence. They were provided with a personalized, illustrated daily medication schedule (Pictur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Two were delivered via a smartphone app 79,80 , 1 was accessed via a digital tablet 81 whilst the remainder were paperbased medication schedules. Six of the 12 studies reported statistically significant adherence outcomes [79][80][81][82][83][84] . Of the 2 studies reporting illness belief outcomes, 1 was effective 80 .…”
Section: ) Medication Reminder Interventionsmentioning
confidence: 99%
“…Two were delivered via a smartphone app 79,80 , 1 was accessed via a digital tablet 81 whilst the remainder were paperbased medication schedules. Six of the 12 studies reported statistically significant adherence outcomes [79][80][81][82][83][84] . Of the 2 studies reporting illness belief outcomes, 1 was effective 80 .…”
Section: ) Medication Reminder Interventionsmentioning
confidence: 99%
“…In five studies, 47,50,51,68,69 education followed assessment of anticholinergic risk, 47 safe management of medicines, 50 ability to manage medicines, 51 diabetes self‐care abilities 69 and comprehensive assessment 68 . Education was delivered both one to one 39–41,45,48–53,55,59,60,64,66,68,70,71 and in groups 42,54,56,60,67 . Techniques and tools included coaching, 41,48,49,66 role play, 54 teach‐back/show‐back, 53,60,66 group discussion, 58,60 dilemma scenarios, 58,60 pictorial information or visual maps, 53,60,62,66 video tutorials, 62 apps and software 47,58,69 .…”
Section: Resultsmentioning
confidence: 99%
“…Education was delivered both one to one 39–41,45,48–53,55,59,60,64,66,68,70,71 and in groups 42,54,56,60,67 . Techniques and tools included coaching, 41,48,49,66 role play, 54 teach‐back/show‐back, 53,60,66 group discussion, 58,60 dilemma scenarios, 58,60 pictorial information or visual maps, 53,60,62,66 video tutorials, 62 apps and software 47,58,69 . In only three interventions 58,60,62 was the educational material codesigned or pretested by either patients or relevant stakeholders.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is so important to ensure proper care and understanding, in particular for this group of patients. By introducing proper education, it is possible to help elderly patients take their medicines more efficiently [29]. It is confirmed that seniors often do not follow recommendations of the physician and pharmacist.…”
Section: Introductionmentioning
confidence: 99%